2015
DOI: 10.1084/jem.20141442
|View full text |Cite
|
Sign up to set email alerts
|

Restricted dendritic cell and monocyte progenitors in human cord blood and bone marrow

Abstract: Liu, Nussenzweig, and colleagues track the differentiation of human progenitor cells into dendritic cells (DCs). They show that a granulocyte/monocyte/DC progenitor gives rise to a monocyte-DC progenitor that in turn gives rise to both monocytes and a common DC progenitor. The common DC progenitor produces the three major subsets of human DCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
271
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(296 citation statements)
references
References 60 publications
(125 reference statements)
16
271
0
1
Order By: Relevance
“…We recently described the human (h)MODP 15 and noted that its cell surface phenotype was similar to that of the hCDP that was described shortly before that 28 ( Figure 7H). Both progenitor populations are very rare, representing about 0.2% of total BM ( Figure 7I).…”
Section: Comparison Of Cdp and Mdp With Modp And Mop: Differentiationmentioning
confidence: 58%
See 2 more Smart Citations
“…We recently described the human (h)MODP 15 and noted that its cell surface phenotype was similar to that of the hCDP that was described shortly before that 28 ( Figure 7H). Both progenitor populations are very rare, representing about 0.2% of total BM ( Figure 7I).…”
Section: Comparison Of Cdp and Mdp With Modp And Mop: Differentiationmentioning
confidence: 58%
“…These data, together with gene expression profiling, confirmed without bias the existence of the MODP and MOP and their developmental relationship. They also revealed that the mouse 23,24 and human 28 CDP populations are similar, respectively identical to the MODP, and that the mouse MDP population 22 is partially overlapping with the MOP and indeed devoid of DC potential.…”
Section: C-fmsmentioning
confidence: 93%
See 1 more Smart Citation
“…34,35 This population was detected in the BM of BRGSF mice (supplemental Figure 2B), and its frequency and total numbers increased following Flt3L treatment (supplemental Figure 2C). These data suggest that the increased frequency and absolute numbers of myeloid cells in Flt3L-treated BRGSF HIS mice may result from an increase in the CD34…”
Section: Resultsmentioning
confidence: 99%
“…Protocols to differentiate moDC use purification of CD14 + blood cells, and most likely omit dedicated DC precursors, which circulate in human peripheral blood in low numbers. These blood‐borne pre‐DC can be induced to differentiate into bona fide DC ex vivo 60, 61. For future DC‐based immunotherapy, it will be of interest to compare the tolerogenic potential of preDC‐derived DC and monocyte‐derived DC generated ex vivo with or without VD3.…”
Section: Vd3‐programmed DC For Immune Therapymentioning
confidence: 99%